Bosnia-Herzegovina: The Role of the Judiciary in a Divided Society - Joseph Marko (Constitutional Review, 2019)
This paper analyzes the role of the Constitutional Court of Bosnia and Herzegovina for the promotion of social justice under the conditions of a triple transformation from war to peace and from a communist regime based on the Titoist self-management ideology to a liberal-democratic political regime and economic market system in three parts. The first section describes the political, constitutional and economic context during and after the collapse of the former Socialist Federal Republic of Yugoslavia and the war in Bosnia-Herzegovina. The second section describes and analyzes the constitutional and institutional arrangements established under the General Framework Agreement for Peace, concluded in Dayton/Ohio and Paris, 1995. The third section deals with the role of the Constitutional Court and analyzes with reference to its case law the interpretative doctrines developed in its adjudication of the right to property concerning different concepts of property and the right to work in the context of the constitutionally guaranteed right to return of refugees and restitution of property.